2018
DOI: 10.1136/oemed-2018-105151
|View full text |Cite
|
Sign up to set email alerts
|

Physical work demands and psychosocial working conditions as predictors of musculoskeletal pain: a cohort study comparing self-reported and job exposure matrix measurements

Abstract: ObjectivesDetermining exposure to occupational factors by workers’ job titles is extensively used in epidemiological research. However, the correspondence of findings regarding associations to health between job exposure matrices (JEMs) and individual-level exposure data is largely unknown. We set out to examine the prospective associations of physical work demands and psychosocial working conditions with musculoskeletal pain, comparing JEMs with individual-level self-reported exposures.MethodsWe analysed data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 37 publications
4
52
0
1
Order By: Relevance
“…Consistent with previous studies (Coggon et al 2013;Neupane et al 2017;Haukka et al 2012;Madsen et al 2018) we found a rather strong positive association between selfreported high OPA and MSP. Eldercare workers are regularly exposed to manual handling activities such as lifting, pulling, and pushing activities, in an awkward body position, which have some causal relationship with musculoskeletal pain (da Costa and Vieira 2010).…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
“…Consistent with previous studies (Coggon et al 2013;Neupane et al 2017;Haukka et al 2012;Madsen et al 2018) we found a rather strong positive association between selfreported high OPA and MSP. Eldercare workers are regularly exposed to manual handling activities such as lifting, pulling, and pushing activities, in an awkward body position, which have some causal relationship with musculoskeletal pain (da Costa and Vieira 2010).…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
“…Occupational groups were classified according to the Danish version of the ISCO-88 classification (DISCO-88). The intraclass correlation coefficient (ICC) for the JEM was 0.30 which is satisfactory compared to other JEM-based exposures for psychosocial work environment factors [47]. The occupations with the lowest and highest levels of job control are presented in Table S2.…”
Section: Exposure Variable: Job Controlmentioning
confidence: 80%
“…The predicted level of job control was assessed using a Job Exposure Matrix (JEM). JEMs were first used in work environment studies in the 1980s [41], and recently, several studies on the development or application of JEMs have been published from Finland, France, the Netherlands, Denmark and Germany [42][43][44][45][46][47]. In countries such as Denmark with population based administrative registers, JEMs enable studies of associations between work environment and health in nationwide cohorts.…”
Section: Exposure Variable: Job Controlmentioning
confidence: 99%
“…Job-exposure matrices are well established to reflect job exposures for various research questions including the association of job exposures to subjective health, injuries, early retirement, lifestyle factors, and health behaviour [4,12,14,15]. It has been shown for single exposures and diseases that the use of job-exposure matrices can provide similar results as the individual assessment of work-related exposures [42][43][44].…”
Section: Limitationsmentioning
confidence: 99%